Policentrizmus, nagyvárosi terek Magyarországon és világszerte - Pintér, Tibor (Acta Scientiarum Socialium, 2011)
Polycentrism, Metropolitan Spaces in Hungary and Worldwide The polycentrism and the networking of cities, more likely the formation of city networks at the same hierarchy level has attracted the attention of actors and legislatures of the European Union, this is the reason why the regional politics have taken steps in that direction in the past 10-15 years. The essence of the change of emphasis was that the regions, as next to or at the expense of subnational, in more cases as international border crossing regional entities, the concept of urban areas has appeared in political/legal documents. In my opinion its most important cause is that the conclusions drawn from economical researches clearly specified these areas as the motors of the economic growth. In this paper I am dealing with the connection between the economic growth and the role of regions.
Keywords: polycentrism; European Union; regional politics; regional entities